Retinal signs and risk of incident dementia in the Atherosclerosis Risk in Communities study. Issue 3 (12th November 2018) - Deal, Jennifer A.; Sharrett, A. Richey; Albert, Marilyn; Bandeen‐Roche, Karen; Burgard, Sheila; Thomas, Sonia Davis; Gottesman, Rebecca F.; Knopman, David; Mosley, Thomas; Klein, Barbara; Klein, Ronald
Abstract: Introduction: The easily‐imaged retinal microvasculature may reflect the brain microvasculature and therefore be related to dementia. Methods: In a population‐based study of 12, 482 adults aged 50‐73 years (22% African American), we estimated the relationship of retinal characteristics from fundus photography (1993‐1995) with incident all‐cause dementia (1993‐1995 to 2011‐2013) and with etiologic subtype of dementia/mild cognitive impairment (2011‐13). Results: A total of 1259 (10%) participants developed dementia over a mean 15.6 years. Moderate/severe (vs. no) retinopathy (hazard ratio [HR], 1.86; 95% confidence interval [CI]: 1.36–2.55) and central retinal arteriolar equivalent (narrowest quartile vs. widest three quartiles; HR, 1.26; 95% CI: 1.09–1.45) were associated with all‐cause dementia. Results were qualitatively stronger (but not statistically significantly different) in participants with diabetes. Retinopathy was associated with a joint outcome of cerebrovascular‐related, but not Alzheimer's disease–related, dementia/mild cognitive impairment (HR, 2.29; 95% CI: 1.24–4.23). Discussion: Exploration of measures in the eye may provide surrogate indices of microvascular lesions relevant to dementia.